A catalyst carrier, preparation method thereof and application thereof
By adding fluoropolymer and alkali metal hydroxycarboxylate to the catalyst support and adopting specific molding and treatment steps, the problems of poor water resistance and low activity of the catalyst support are solved, and high activity, high selectivity and long-term A catalyst with lifespan, suitable for the industrial production of allyl acetate.
Patent Information
- Application Number
- CN202310001882.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-01-03
AI Technical Summary
During the preparation and application of existing catalyst support, there are problems such as poor water resistance, low activity and selectivity, and short service life. Especially in the industrial production of allyl acetate, there is a catalyst bed pressure drop and active components loss. etc.
By preparing a mixed oxide containing SiO2 and Al2O3 as a carrier, and adding fluoropolymer and specific alkali metal hydroxycarboxylate as treatment agents during the carrier molding process, water resistance is formed through steps such as aging, drying, and calcining. Good catalyst support.
The crack resistance and pore structure distribution of the catalyst support in water is realized, the activity, selectivity and service life of the catalyst are improved, and it is suitable for the efficient preparation of allyl acetate.
Smart Images

Figure BDA0004034257660000051 
Figure BDA0004034257660000081 
Figure BDA0004034257660000082
Abstract
Description
Technical Field
[0001] The invention relates to a porous catalyst carrier, which is used for producing catalysts for acetyl oxidation and belongs to the technical field of catalyst carrier preparation. Background Art
[0002] Silica gel is widely used as a catalyst carrier. It has high strength, good acid resistance and heat resistance. It is used in catalysts such as olefin oxyacylation and olefin hydration, especially in the production of vinyl acetate by ethylene oxyacylation and the production of allyl acetate by propylene oxyacylation.
[0003] In the 1980s, Showa Denko of Japan first realized the industrial production of allyl acetate. Showa Denko developed the acetyl oxidation technology, using propylene, oxygen and acetic acid as raw materials in the presence of palladium and a co-catalyst, and using a fixed bed gas phase reaction to prepare allyl acetate. The acetyl oxidation catalyst used is supported by SiO2, Al2O3 or a mixture of SiO2 and Al2O3.
[0004] The patent with publication number CN 102227260 B records an open-pore catalyst carrier made of a material including natural layered silicate and ZrO2. The catalyst carrier is made of a material including natural layered silicate and tetragonal modified ZrO2, and the catalyst carrier can be used as a catalyst for synthesizing (chain) alkenyl acetate. The catalyst carrier uses natural minerals as raw materials, and it is difficult to ensure the batch stability of the catalyst carrier index. In addition, a large amount of inorganic acid treatment is required during the production process, which is not friendly to the environment and is not conducive to its large-scale application in industry.
[0005] The patent with publication number CN 101730585B describes a porous catalyst carrier for producing vinyl acetate monomer, which includes a natural layered silicate and ZrO2. The catalyst carrier requires acid treatment, calcination and other methods for the natural layered silicate, and adds zirconium oxide treatment, which has a complicated preparation process, high production cost and is not economical for industrial application.
[0006] The patent with publication number CN 202570186 U describes a carrier of an allyl acetate catalyst. The carrier is made of SiO2, Al2O3 or a mixture thereof, is a spherical particle, and has arched grooves. The catalyst carrier is a special-shaped carrier that can reduce the pressure drop of the catalyst bed. However, due to the presence of the grooves, the carrier is prone to catalyst wear and loss of active components, which is not conducive to industrial application. Summary of the invention
[0007] An object of the present invention is to provide a method for preparing a catalyst carrier, wherein the catalyst carrier has good water resistance and after being prepared into a catalyst, the catalyst has high activity and selectivity and a longer service life.
[0008] Another object of the present invention is to provide an application of the above-mentioned catalyst carrier in an oxyacylation catalyst, in particular, a catalyst for preparing an allyl acetate compound. The preparation of allyl acetate under the action of the catalyst carrier provided by the present invention has the characteristics of high activity, high selectivity and long life.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a catalyst carrier comprises the following steps:
[0011] 1) Raw material crushing: crush SiO2, Al2O3 or their mixed oxides into powders of a certain size; crush a certain amount of pore-forming agent into powders of a certain size; mix the two in a certain proportion;
[0012] 2) Carrier molding: adding a certain amount of binder, and rolling the powder mixed in step 1) into balls through a granulator;
[0013] 3) Aging and shaping: placing the spherical carrier obtained in step 2) in a sealed container, aging at a certain aging temperature for a certain period of time;
[0014] 4) Drying and calcining: drying the catalyst carrier after aging in step 3) at a certain temperature and humidity, and calcining the dried sample at a certain temperature;
[0015] 5) Surface modification: prepare a certain amount of treatment agent, impregnate it onto the catalyst carrier of step 4), and dry it to obtain the finished catalyst carrier.
[0016] Further, in step 1, the particle size of the crushed oxide powder is 10-300 μm, preferably 50-250 μm;
[0017] The particle size of the crushed pore-forming agent powder is 0.1-100 μm, preferably 0.2-80 μm; the pore-forming agent is at least one of fluorine-containing polymers such as polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polychlorotrifluoroethylene-vinylidene fluoride copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-hexafluoroisobutylene copolymer, etc., preferably polyvinylidene fluoride and vinylidene fluoride-trifluorochloroethylene copolymer; the amount of the pore-forming agent added is 0.2%-10% of the mass of the oxide, preferably 0.5%-8%.
[0018] Furthermore, the binder in step 2 is silica sol, alumina sol or a mixture of the two, the mass concentration of silicon dioxide contained in the silica sol or the aluminum oxide contained in the alumina sol is 5-50%, preferably 10-40%; the amount of the binder added is 0.2 times to 3 times the mass of the mixed powder, preferably 0.5 times to 2.8 times.
[0019] Furthermore, in step 3, the aging temperature is 5°C-60°C, preferably 20°C-55°C, and the aging time is 8h-240h, preferably 12h-200h.
[0020] Furthermore, in step 4, the drying temperature is 5°C-60°C, preferably 20°C-55°C, the drying relative humidity is 40%-90%, preferably 45%-80%; the roasting temperature is 300°C-800°C, preferably 400°C-750°C.
[0021] The inventors have found that the size of the raw material after crushing, the amount of binder added, the ratio of binder added, the aging temperature and time, the drying temperature and humidity, and the calcination temperature will affect the rate of the catalyst carrier not cracking in water and the pore structure distribution. If the size of the raw material after crushing is too large and the amount of binder added is too little, the strength of the catalyst carrier after rolling into balls will be low and it will be easy to burst in water; if the aging temperature is too high, the drying temperature is too high, and the humidity is too high, it is easy to cause the surface of the catalyst carrier to crack, the strength of the catalyst carrier is too low, and it is easy to burst in water.
[0022] Furthermore, the treating agent in step 5 is an alkali metal hydroxycarboxylate, and the number of carbon atoms contained in the alkali metal hydroxycarboxylate is greater than 2; the alkali metal hydroxycarboxylate includes but is not limited to at least one of potassium / sodium / cesium hydroxycitrate, potassium / sodium / cesium hydroxyhexanoate, potassium / sodium / cesium hydroxyvalerate, potassium / sodium / cesium hydroxybutyrate, potassium / sodium / cesium hydroxypropionate, and potassium / sodium / cesium hydroxybenzoate; the treating agent is added in an amount of 2%-20% of the mass of the catalyst carrier, preferably 5%-15%.
[0023] Furthermore, the catalyst carrier has a specific surface area of 100-300m 2 / g, pore volume 0.3-1.2mL / g, average mesopore diameter 8-20nm, average macropore diameter 50-500nm;
[0024] Preferably, the carrier has a specific surface area of 120-280 m 2 / g, more preferably 150-250m 2 / g; pore volume is 0.4-1.0mL / g, more preferably 0.6-0.9mL / g; average mesopore diameter is 9-17nm, more preferably 10-16nm; average macropore diameter is 60-400nm, more preferably 70-300nm.
[0025] The present invention also relates to the use of the catalyst carrier in preparing a catalyst, in particular a catalyst for acyl oxidation.
[0026] Furthermore, the active component of the catalyst for acyl oxidation mainly contains Pd, Au, Cu and Sn as chemical components, and the catalyst can be prepared by the method of the prior art. The catalyst for acyl oxidation is used to prepare vinyl acetate.
[0027] The present invention has the following beneficial effects:
[0028] 1) The catalyst carrier of the present invention is not easy to explode in water after calcination and molding (the rate of non-cracking of the catalyst carrier in water is not less than 90%). Fluorine-containing polymer is added during the molding process, and the fluorine-containing polymer decomposes during the calcination process to produce a macroporous structure. The trace amount of hydrogen fluoride produced by the decomposition can expand the mesoporous structure of the carrier to produce a hierarchical pore structure including mesopores and macropores, which is beneficial to the diffusion of high molecular weight products produced during the reaction and improves the service life of the catalyst.
[0029] 2) The treating agent added to the catalyst carrier of the present invention is a specific alkali metal hydroxycarboxylate. The addition of the treating agent can effectively form a synergistic effect with the active component, the active component is not easy to be lost, and the prepared catalyst has high activity and selectivity and a longer service life.
[0030] 3) The catalyst carrier of the present invention is used for the preparation of oxyacylation catalysts, in particular, catalysts for preparing allyl acetate compounds. Compared with existing catalysts, the catalyst prepared on the carrier provided by the present invention has the characteristics of high activity, high selectivity and long life, and is more competitive in industrial applications. DETAILED DESCRIPTION
[0031] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0032] The test methods and calculation methods used in the embodiments or comparative examples are as follows:
[0033] 1. Determination method of specific surface area and pore structure information of catalyst carrier
[0034] The mesoporous structure of the catalyst support was determined by N2 physical adsorption method, the specific surface area was obtained by BET method, and the pore volume was obtained by BJH desorption method; the mesoporous structure of the catalyst support was determined by mercury intrusion method.
[0035] 2. Determination method of non-explosion rate of catalyst carrier in water
[0036] Take out 100 catalyst carrier particles, soak them in deionized water for 30 minutes, and then count the proportion of the number of catalyst carrier particles that do not explode to the total number, which is the non-explosion rate of the catalyst carrier in water.
[0037] 3. Use gas chromatography and Agilent GC 8890A chromatograph to analyze the content of each component in the reaction product, and calculate the activity (space-time yield of the target product, referred to as STY value) and selectivity of the catalyst according to the following formula:
[0038]
[0039] [Example 1]
[0040] 1) Preparation of catalyst carrier
[0041] Take coarse-porous silica gel and crush it with a crusher to screen out 1.5 kg of powder with a particle size of 75-150 μm, take polyvinylidene fluoride particles, crush the polyvinylidene fluoride particles with a ball mill, and screen out 78 g of powder with a particle size of 0.5-20 μm, mix the screened silica gel powder and polyvinylidene fluoride powder evenly, and then add them to a granulator. At a certain speed, add 1.2 kg of silica sol with a silicon dioxide concentration of 10%, and roll them into 4-6 mm small balls; put the small balls into a sealed tank at room temperature The pellets were aged for 144 hours under the following conditions: then the pellets were taken out and placed in a drying oven, and dried under the conditions of relative humidity of 65% and temperature of 40°C. The dried pellets were placed in a muffle furnace and calcined at 550°C for 4 hours to obtain water-resistant carrier pellets; then 150 g of tripotassium 2-hydroxycitrate was prepared into a solution, which was impregnated on the water-resistant carrier and dried sufficiently to obtain a catalyst carrier; 100 pellets of the prepared catalyst carrier were taken and placed in water with a non-cracking rate of 100%; the physical properties of the catalyst carrier are shown in Table 1.
[0042] 2) Preparation and evaluation of catalysts
[0043] Take 1L of catalyst carrier, prepare 420mL of aqueous solution of sodium chloropalladate and cupric chloride containing 5.0g Pd and 0.9g Cu, stir well, add to the catalyst carrier, and dry well; then, introduce 5% hydrogen and nitrogen mixed gas at 180°C for 8h to reduce, and obtain the finished catalyst.
[0044] 500 mL of the finished catalyst was placed in a fixed bed reactor with an inner diameter of 3 cm and a height of 150 cm. The reaction temperature was 145-160 ° C, the reaction pressure was 0.75 MPaG, and the raw material volume space velocity was 2000 h -1 The raw material composition is propylene: acetic acid: oxygen: water = 1: 0.3: 0.25: 0.35 (molar ratio). The evaluation results of the catalyst are shown in Table 2.
[0045] [Example 2]
[0046] 1) Preparation of catalyst carrier
[0047] The coarse-pored silica gel was crushed with a crusher to screen out 1.5 kg of powder with a particle size of 100-200 μm. The vinylidene fluoride-chlorotrifluoroethylene copolymer particles were crushed with a ball mill to screen out 43 g of powder with a particle size of 1-10 μm. The screened silica gel powder and vinylidene fluoride-chlorotrifluoroethylene copolymer powder were mixed evenly and added to a granulator. At a certain speed, 1.5 kg of silica sol with a silicon dioxide concentration of 15% was added to the granulator and rolled into 4-6 mm small pieces. The small balls were placed in a sealed tank at room temperature and aged for 96 hours; then the small balls were taken out and placed in a drying oven, and the small balls were dried under the conditions of relative humidity of 80% and temperature of 55°C, and the dried small balls were placed in a muffle furnace and roasted at 650°C for 4 hours to obtain water-resistant carrier small balls; then 108g of potassium 2-hydroxypropionate was prepared into a solution, impregnated on the water-resistant carrier, and the catalyst carrier was obtained after sufficient drying; 100 pellets of the prepared catalyst carrier were taken and placed in water with a crack-free rate of 98%. The physical properties of the catalyst carrier are shown in Table 1.
[0048] 2) Preparation and evaluation of catalysts
[0049] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0050] [Example 3]
[0051] 1) Preparation of catalyst carrier
[0052] Take coarse-porous silica gel and crush it with a crusher to screen out 1.5 kg of powder with a particle size of 50-180 μm; take polyvinylidene fluoride particles and crush them with a ball mill to screen out 120 g of powder with a particle size of 10-45 μm; the screened silica gel powder and polyvinylidene fluoride powder are mixed evenly and added to a granulator; at a certain speed, the granulator adds 0.80 kg of silica sol with a silica concentration of 7% and rolls it into 4-6 mm small balls; put the small balls into a sealed tank at room temperature and age for 200 hours; then take out the small balls, put them into a drying oven, dry the small balls under a relative humidity of 45% and room temperature, put the dried small balls into a muffle furnace, and roast them at 600° C. for 4 hours to obtain water-resistant carrier small balls; then take 189 g of potassium 2,3,4-trihydroxybutyrate to prepare a solution, impregnate it on the water-resistant carrier, and obtain a catalyst carrier after sufficient drying; take 100 prepared catalyst carriers and put them into water without cracking with a rate of 99%. The physical properties of the catalyst carrier are shown in Table 1.
[0053] 2) Preparation and evaluation of catalysts
[0054] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0055] [Comparative Example 1]
[0056] 1) Preparation of catalyst carrier
[0057] No polyvinylidene fluoride powder was added during the preparation of the catalyst support, and the remaining preparation conditions were the same as those in Example 1. The physical properties of the catalyst support are shown in Table 1.
[0058] 2) Preparation and evaluation of catalysts
[0059] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0060] [Comparative Example 2]
[0061] 1) Preparation of catalyst carrier
[0062] During the preparation of the catalyst support, the impregnation operation of tripotassium 2-hydroxycitrate was not performed, and the remaining preparation conditions were the same as those in Example 1. The physical properties of the catalyst support are shown in Table 1.
[0063] 2) Preparation and evaluation of catalysts
[0064] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0065] [Comparative Example 3]
[0066] 1) Preparation of catalyst carrier
[0067] During the preparation of the catalyst support, polyvinylidene fluoride powder was not added, and the impregnation operation of tripotassium 2-hydroxycitrate was not performed. The remaining preparation conditions were the same as those in Example 1. The physical properties of the catalyst support are shown in Table 1.
[0068] 2) Preparation and evaluation of catalysts
[0069] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0070] [Comparative Example 4]
[0071] 1) Preparation of catalyst carrier
[0072] During the preparation of the catalyst support, an equal mass of potassium 2-hydroxyacetate was used to replace tripotassium 2-hydroxycitrate, and the remaining preparation conditions were the same as those in Example 1. The physical properties of the catalyst support are shown in Table 1.
[0073] 2) Preparation and evaluation of catalysts
[0074] The preparation and evaluation conditions of the catalyst were the same as those in Example 1. The evaluation results of the catalyst are shown in Table 2.
[0075] Table 1 Catalyst carrier properties
[0076]
[0077] Table 2 Catalytic performance evaluation table of catalyst
[0078]
[0079] From the above test results we can see that:
[0080] As can be seen from Table 2, after adding the treatment agent and fluoropolymer to the carrier, the initial activity, selectivity and service life of the prepared catalyst are significantly improved. Compared with the comparative example, in Example 1, after running for 100 hours, the catalyst prepared with the carrier added with the treatment agent is better than the catalyst prepared with the carrier without the treatment agent added. After running for 3000 hours, the activity and selectivity of the catalyst prepared by the carrier without the addition of the fluoropolymer in Comparative Example 1 are significantly reduced, indicating that the high molecular weight products produced by the reaction are not completely diffused, covering the catalyst active sites, resulting in reduced catalyst activity and selectivity; Comparative Example 3 shows that the initial activity and service life of the catalyst prepared by the carrier without the addition of the treatment agent and fluoropolymer are the lowest. Comparative Example 4 shows that after adding the 2-hydroxyacetic acid potassium treatment agent and fluoropolymer to the carrier, the prepared catalyst has a high activity after running for 100 hours, but after a long time of 3000 hours, the activity and selectivity of the catalyst are significantly reduced, indicating that the catalyst performance is reduced due to long-term use.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst carrier, characterized in that: The following steps are involved: 1) Raw material crushing: crush SiO2, Al2O3 or their mixed oxides into powders of a certain size, crush the pore-forming agent into powders of a certain size, and mix the two uniformly in a certain ratio; the pore-forming agent is at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polychlorotrifluoroethylene-vinylidene fluoride copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and vinylidene fluoride-hexafluoroisobutylene copolymer; the crushed oxide powder has a particle size of 10-300 μm; the crushed pore-forming agent powder has a particle size of 0.1-100 μm; 2) Carrier molding: adding a certain amount of binder, rolling the powder mixed in step 1) into balls; the amount of binder added is 0.2 to 3 times the mass of the mixed powder; 3) Aging and shaping: the spherical carrier obtained in step 2) is placed in a sealed container and aged for a certain period of time at 5°C-60°C; 4) Drying and calcining: drying the aged catalyst carrier in step 3) at a certain temperature and humidity, and then calcining at a certain temperature; wherein the drying temperature is 5°C-60°C, the drying relative humidity is 40%-90%, and the calcining temperature is 300°C-800°C; 5) Surface modification: prepare a certain amount of treatment agent, impregnate it onto the catalyst carrier of step 4), and dry it to obtain a finished catalyst carrier; the treatment agent is an alkali metal hydroxycarboxylate, and the carbon number of the alkali metal hydroxycarboxylate is greater than 2.
2. The method for preparing a catalyst carrier according to claim 1, characterized in that: The amount of the pore former added is 0.2%-10% of the oxide mass.
3. The method for preparing a catalyst carrier according to claim 1, characterized in that: In step 2), the binder is silica sol, aluminum sol or a mixture of the two, and the mass concentration of the silica sol is 5-50%.
4. The method for preparing a catalyst carrier according to claim 1, characterized in that: The aging time in step 3) is 8h-240h.
5. The method for preparing a catalyst carrier according to claim 1, characterized in that: The alkali metal hydroxycarboxylate is selected from at least one of potassium / sodium / cesium hydroxycitrate, potassium / sodium / cesium hydroxycaproate, potassium / sodium / cesium hydroxyvalerate, potassium / sodium / cesium hydroxybutyrate, potassium / sodium / cesium hydroxypropionate, and potassium / sodium / cesium hydroxybenzoate.
6. The method for preparing a catalyst carrier according to claim 1 or 5, characterized in that: The amount of the treating agent added is 2%-20% of the mass of the catalyst carrier.
7. A catalyst carrier prepared by the preparation method according to any one of claims 1 to 6.
8. The catalyst carrier according to claim 7, wherein the catalyst carrier has a specific surface area of 100-300 m 2 / g, pore volume 0.3-1.2mL / g, average mesopore diameter 8-20nm, average macropore diameter 50-500nm.
9. Use of the catalyst carrier prepared by the preparation method according to any one of claims 1 to 6 or the catalyst carrier according to claim 7 or 8 in producing a catalyst, wherein the catalyst is an acyl oxidation catalyst.
10. The use according to claim 9, wherein the catalyst for acyl oxidation is used to prepare vinyl acetate.
11. The use according to claim 9 or 10, characterized in that: The active component of the acyl oxidation catalyst comprises at least one of Pd, Au, Cu and Sn.
Citation Information
Patent Citations
Zirconium-doped catalyst support, method for producing the same and catalyst containing a zirconium-doted catalyst support
CN101730585B
Catalyst carrier, method for production thereof, and use thereof
CN102227260B
Carrier used for allyl acetate catalysts
CN202570186U
Fluidized bed isomerization catalyst, and preparation method and applications thereof
CN107537526A
Modified alpha-alumina carrier and preparation method thereof, and silver catalyst and applications thereof
CN108686712A